Between sin and crime: The administration of justice and the documentary limits for the study of sodomy in the Viceroyalty of Peru (16th-17th centuries) - Molina, Fernanda (2008)
The study of the phenomena associated with sexuality in the past represents a challenge for contemporary researchers, to the extent that the sources related to these issues are, by their very nature, scarce or difficult to access. The work explores the causes of this documentary scarcity regarding male sodomy in the Peruvian viceroyalty society between the 16th and 17th centuries. However, beyond recognizing the cryptic nature of the phenomenon —both due to its unspeakable and aberrant character and because it is an experience of the intimate and private life of individuals—, the research suggests that these limitations responded not only to the nature of the phenomenon but, to a great extent, to the logic and organizational foundations of the institutions in charge of producing information on sodomitic sexual practices, that is, to the actions of the courts responsible for the administration of justice.